Influence of test duration and event specificity on maximal accumulated oxygen deficit of high performance track cyclists - Craig, N. P.; Norton, K. I.; Conyers, R. A.; Woolford, S. M.; Bourdon, P. C.; Stanef, T.; Walsh, C. B (International Journal of Sports Medicine, 1995)
This study examined the relationship between the time required to fully utilise the maximal accumulated oxygen deficit (MAOD) and event specificity of track cyclists. Twelve track endurance and 6 sprint high performance track cyclists performed four treatments of 70 s, 120 s, 300 s and 115% VO2max of maximal cycling on an air-braked ergometer. Peak blood lactate was measured immediately after each test with VO2 kinetics being assessed during the 115% VO2max time to exhaustion test. When the two cycling groups were combined there was no significant difference in the MAOD when assessed under the four different exercise durations. However, when the groups were analysed separately the following results were apparent: (1) the sprint cyclists achieved a significantly greater MAOD (66.9 +/- 2.2 ml.kg-1) compared to the track endurance cyclists (57.6 +/- 6.7 ml.kg-1) when a 70 s test duration was employed (2) even though the track endurance cyclists achieved their greatest MAOD during the 300 s test protocol (62.1 +/- 11.0 ml.kg-1), it was not significantly different to the MAOD's measured during the three other test durations and (3) the sprint cyclists recorded their greatest MAOD during the 70 s supramaximal test protocol (66.9 +/- 2.2 ml.kg-1). This was not significantly different to the 120 s test MAOD, but it was significantly higher than the MAOD values recorded during the 115% VO2max and 300 s test durations. There was no significant difference between the two groups in the peak post-exercise blood lactate concentrations for any of the tests and only the 70 s test produced a significant correlation between peak blood lactate and the MAOD. The VO2 kinetics (VO2 t1/2) of the sprinters was significantly slower than that of the track endurance cyclists (26.3 +/- 2.3 vs 23.9 +/- 2.8 s.). The findings of this study demonstrate that sprint cyclists can fully express their anaerobic capacity within an event specific 70 s all-out test and that these cyclists progressively decrease their anaerobic capacity during a 120 s, 115% VO2max (mean time = 210 s) or 300 s test, despite giving all-out efforts. Conversely, track endurance cyclists achieve their highest mean score during an event specific 300 s test and their lowest during a 70 s test. These findings have important implications when testing high performance cyclists for determination of MAOD, with the implication that it is necessary to assess MAOD under exercise conditions (i.e., duration, pacing) specific to the cyclist's chosen event.